A Case Study on the Power-Aware Protocol Framework for Wireless Sensor Networks. (17th December 2013) - Díaz, Pedro; Royo, Fernando; Olivares, Teresa; Ramirez-Mireles, Fernando; Orozco-Barbosa, Luis
Abstract : The proliferation of wireless sensor networks is one of the main hardware components enabling the creation of the Internet of Things. As sensor nodes are being deployed in a wide variety of indoor and outdoor environments, they are in general battery-powered devices. In fact, power provisioning is one of the main challenges faced by engineers when deploying IoT-based applications. This paper develops crosslayer architecture, integrating smart and power-aware protocols with a low-cost and high-efficiency power management module, which is the basis of long-lasting of self-powered WSNs. The main physical components of the proposed architecture are a wireless node comprising a set of small solar cells responsible for harvesting the energy and an ultracapacitor as storage device. Energy consumption is reduced significantly by varying the sleep/wake duty cycle of the radio module. For environments with only a few hours of sunlight per day we present the feasibility of ensuring long-lasting operation by means of adapting the duty cycle scheme according to the energy stored in the ultracapacitor. Our experiments prove the feasibility of a long-endurance outdoors operation with a low-complexity power management unit. This is an important advance towards the development of novel IoT-based applications.